2022
DOI: 10.1136/bmjopen-2021-057914
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of COVID-19 knowledge, beliefs and prevention behaviours among adults in Senegal

Abstract: ObjectivesThe aim of the study was to explore COVID-19 beliefs and prevention behaviours in a francophone West African nation, Senegal.DesignThis was a cross-sectional analysis of survey data collected via a multimodal observational study.ParticipantsSenegalese adults aged 18 years or older (n=1452).Primary and secondary outcome measuresPrimary outcome measures were COVID-19 prevention behaviours. Secondary outcome measures included COVID-19 knowledge and beliefs. Univariate, bivariate and multivariate statist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
0
1
Order By: Relevance
“…Social distancing and staying at home were also registered although to a lower degree. Our results were in contradiction with those of Kearney et al who observed high compliance with recommended COVID-19 prevention behaviors among their sample of Senegal respondents, particularly for masking and personal hygiene practices [51]. This difference could be explained by the fact that our study population is younger and less inclined to comply with preventive measures [52, 53].…”
Section: Discussioncontrasting
confidence: 99%
“…Social distancing and staying at home were also registered although to a lower degree. Our results were in contradiction with those of Kearney et al who observed high compliance with recommended COVID-19 prevention behaviors among their sample of Senegal respondents, particularly for masking and personal hygiene practices [51]. This difference could be explained by the fact that our study population is younger and less inclined to comply with preventive measures [52, 53].…”
Section: Discussioncontrasting
confidence: 99%
“…These evolving attitudes reflect the dynamic nature of public opinion towards vaccination in the face of a global health crisis. Furthermore, there was a statistical significance between attitudes, knowledge, and perceptions regarding the COVID-19 vaccine, and this was further supported by a study conducted by M Kearney et al [ 41 ], these results demonstrate the need for identifying and resolving the factors influencing knowledge, attitudes, and perceptions of the COVID-19 vaccines, as well as knowledge of these components, to properly promote vaccine acceptance, respond to concerns, and support public health programs.…”
Section: Discussionsupporting
confidence: 62%